Biomechanical Design of an Anthropomorphic Prosthetic Hand - (:unkn) unknown (IEEE Computer Society, 2018)
The anatomical structure of the hand and its parts; muscles, tendons, bones, and ligaments give the hand its dexterous capabilities in a very efficient way. Studying these structures is important for adapting anthropomorphic features in prosthetic devices. Giving the anthropomorphic features to a prosthetic hand increases the complexity of the mechanical design; therefore, the control of the system. However, we can simplify the mechanical structure of the hand, but still keep the essential functions of the hand with advances in technology. With this motivation, the current study achieves a design for an anthropomorphic hand that imitates a natural hand, taking into account the essential anatomical and functional features. © 2018 IEEE.